Elsewhere, Ideally Nowhere: Shadow Banking and Offshore Finance - Palan, Ronen; Nesvetailova, Anastasia (Politik, 2013)
If we were to identify one common thread across the nancial system’s stages of evolution, it is the quest for being located for tax and regulatory purposes elsewhere or, ideally, nowhere. Recognising the limits of mainstream economic models in providing a comprehensive explanation of this phenomenon, we draw on the ideas of orstein Veblen and his theory of business civilisation. A Veblenian analysis suggests that dynamics and behaviour in nance that are commonly associated with human failure (greed, exuberance, fraud, incompetence), and which appear to have become widespread practice, should best be understood as sabotage. Finance is awash with techniques designed to sabotage both clients and the governments who enacted regulations that were supposed to protect clients. ese techniques are legal mechanisms, albeit as Veblen writes, not in the spirit of the law.